Cardiovascular and oxygen uptake kinetics during sequential heavy cycling exercises - Perrey, S.; Scott, J.; Mourot, L.; Rouillon, J. D. (Canadian Journal of Applied Physiology, 2003)
The purpose of the present study was to assess the relationship between the rapidity of increased oxygen uptake (VO2) and increased cardiac output (CO) during heavy exercise. Six subjects performed repeated bouts on a cycle ergometer above the ventilatory threshold (approximately 80% of peak VO2) separated by 10-min recovery cycling at 35% peak VO2. VO2 was determined breath-by-breath and CO was determined continuously by impedance cardiography. CO and VO2 values were significantly higher during the 2-min period preceding the second bout. The overall responses for VO2 and CO were significantly related and were faster during the second bout. Prior heavy exercise resulted in a significant increase in the amplitude of the fast component of VO2, with no change in the time constant and a decrease in the slow component. Under these circumstances, the amplitude of the fast component was more sensitive to prior heavy exercise than was the associated time constant.